ECTOC (ELECTRICAL CARBON DIOXIDE TO OXYGEN CONVERTER) TO ADD OXYGEN IN THE ROOMS OF BOARDING HOUSES - Anang Prasetyo; Rahmat Widadi; I Wayan Adiyasa (Pelita - Jurnal Penelitian Mahasiswa UNY, 2013)
This research was aimed at finding out the concept of ECTOC (Electrical CarbonDioxide To Oxygen Converter) to add oxygen in in the rooms of boarding houses andfinding out how ECTOC (Electrical Carbon Dioxide To Oxygen Converter) worked toadd oxygen in in the rooms of boarding houses.This research was categorized as Research and Development employing themodel of Borg and Gall. The data were collected through observation, questionnaires,and documentation. The data were analyzed quantitatively and qualitatively. Theanalyzed qualitative data were classified based on the collection category andgeneralized by employing simple statistics.The concept and procedure of ECTOC (Electrical Carbon Dioxide To OxygenConverter) was adding oxygen to refresh the rooms by taking the air from outside andprocessing it in the pipes around which induction with high voltage was wound toburn carbon dioxide and send oxygen to the rooms. The high voltage was obtainedfrom the coil converting 12Volt into